Fifty years of Pakistan's economy : traditional topics and contemporary concerns / edited by Shahrukh Rafi Khan - "Khan , Shahrukh Rafi (ed.)" (New Delhi, 1999)
The volume reviews the fifty years of Pakistan's economy, representing the case history of a country as a laboratory where currently fashionable economic ideas have been imported and tried out.
Keywords: Economic development - Pakistan